CHARACTERISTICS OF DISORDERS OF THE QUALITY OF LIFE OF YOUNG PATIENTS DEPENDING ON THE VARIANT OF THE COURSE OF GASTROESOPHAGEAL REFLUX DISEASE - Gorodnytska, I.M.; Skrypnyk, I.M.; Maslova, G.S. (World of Medicine and Biology, 2023)
The article represents the results of our research on determining the influence of esophageal symptoms of erosive and non-erosive forms of gastroesophageal reflux disease on indicators of the physical and mental components of quality of life according to the Medical Outcomes Study Questionnaire Short-Form 36. The presence and degree of severity of symptoms of gastroesophageal reflux disease were analyzed using the Gastroesophageal Reflux scale Disease Questionnaire. We examined 18 patients with an erosive form and 18 patients with a non-erosive form of gastroesophageal reflux disease. It is shown that against the background of the erosive form of gastroesophageal reflux disease, daily manifestations of the symptoms of the disease are more often observed, namely heartburn (RR=6.00 (0.80-44.95); p>0.05), regurgitation and pain in the epigastric region of the abdomen (RR=2.50 (0.56-11.25); p>0.05), which leads to violations of mainly physical components of quality of life. At the same time, the esophageal symptoms of the non-erosive form of gastroesophageal reflux disease change the quality of life of patients in categories that characterize mental health.